Mathematics learning for school readiness of kindergarteners in the western rural area of china – taking county s as an example - Min Li; Xiaoping Yang (Problemy Wczesnej Edukacji)
Taking 167 kindergarteners just one year before elementary school from 7 different kindergartens in county as an example, this research examined kindergarteners’ math development for school readiness in a rural area of western China. From the research carried out, it was concluded that development in different math abilities are not coordinated, that the children’s performance in number and volume are much better than in geometry and relationship, and that there are significant differences between different kindergartens regarding location and funding – children from independent public kindergartens and private kindergartens, charging expensive tuition fees and located in county towns, are much better than others. Therefore, it is reasonable to assert that math education in rural kindergartens is in urgent need of improvement, with teachers needing to update their ideas and techniques in math education so as to enhance support and guidance in the areas   of geometry and relationship. Also, government must make further effort to improve the condition of educational equity within country areas, which, at this stage, means reinforcing high quality resources such as good teachers in countryside kindergartens.